2016
DOI: 10.1108/ara-11-2014-0115
|View full text |Cite
|
Sign up to set email alerts
|

The value relevance of financial instruments disclosure: evidence from Jordan

Abstract: Purpose The purpose of this paper is to: examine the value relevance of financial instruments disclosure (FID) provided by Jordanian listed companies under International Financial Reporting Standard (IFRS 7) as compared to that supplied under IAS 30/32; provide evidence about the value relevance of high vs low levels of FID; and investigate which components of FI-related information are more value relevant. Design/methodology/approach A sample of 70 Jordanian listed companies is used in this monograph. A dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 55 publications
2
46
1
7
Order By: Relevance
“…Value relevance is also described as the ability of financial statements to explain market value 6 . Value relevance in accounting disclosure is considered as a useful basic determinant of information 7 . According to Article 44, paragraph 1m of the Income Tax Law, the excess of fixed assets revaluation is treated as a tax object, as it is an additional economic resource obtained by the company 8 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Value relevance is also described as the ability of financial statements to explain market value 6 . Value relevance in accounting disclosure is considered as a useful basic determinant of information 7 . According to Article 44, paragraph 1m of the Income Tax Law, the excess of fixed assets revaluation is treated as a tax object, as it is an additional economic resource obtained by the company 8 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The possibility that the variance of the error term might not be constant was accounted for using White's (1980) procedure, and the results indicated that heteroskedasticity was not an issue, since White's correction did not alter the findings. Lastly, the Ramsey Reset test was used to test whether the correct specification of the models was employed (Tahat et al, 2016). The evidence from this Ramsey Reset test suggested that all of the models were correctly specified as linear equations.…”
Section: The Value Relevance Of Segmental Reportingmentioning
confidence: 99%
“…equations by calculating the Variance Inflation Factor (VIF); a value of greater than 10 indicates that a significant amount of collinearity may be present (Tahat et al, 2016). An analysis of Tables 5 and 6 indicates VIF values of between 1 and 5, confirming that multicollinearity is not an issue when interpreting the regression equations.…”
Section: The Value Relevance Of Segmental Reportingmentioning
confidence: 99%
See 2 more Smart Citations